2019
DOI: 10.1371/journal.pone.0214251
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of symptom-based diagnostic HIV testing versus targeted and blanket provider-initiated testing and counseling among children and adolescents in Cameroon

Abstract: Objectives The concurrent implementation of targeted (tPITC) and blanket provider-initiated testing and counselling (bPITC) is recommended by the World Health Organization (WHO) for HIV case-finding in generalized HIV epidemics. This study assessed the effectiveness of this intervention compared to symptom-based diagnostic HIV testing (DHT) in terms of HIV testing uptake, case detection and antiretroviral therapy (ART) enrollment among children and adolescents in Cameroon, where estimated HIV prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 27 publications
1
10
1
Order By: Relevance
“…About 24% of children with unknown status identified through the family index POS were not tested for HIV. However, the percentage of children with unknown status that was not tested (24%) in our study was much lower than the 43.3% reported by Yumo et al for neighboring Cameroon [30]. A major reason for the missed opportunity was that at this POS, the method for getting these children tested was simply to ask parents to return to the clinic with the children, and parents often did not return with their children for HIV testing as scheduled.…”
Section: Plos Onecontrasting
confidence: 77%
“…About 24% of children with unknown status identified through the family index POS were not tested for HIV. However, the percentage of children with unknown status that was not tested (24%) in our study was much lower than the 43.3% reported by Yumo et al for neighboring Cameroon [30]. A major reason for the missed opportunity was that at this POS, the method for getting these children tested was simply to ask parents to return to the clinic with the children, and parents often did not return with their children for HIV testing as scheduled.…”
Section: Plos Onecontrasting
confidence: 77%
“…We showed where the difference lies between the states using a Post-Hoc test which revealed a significant difference in HTS outcome across board (P < 0.05). This finding is consistent with two studies carried out in Cameroon that observed that targeted provider-initiated testing and counselling (PITC) is superior to blanket PITC in HIV case finding in children [8,9]. Findings are also similar to two other studies in Malawi by Simon KR, et al [10] and Saeed A, Rachael AK, et al [11] that shows that in order to improve pediatric case finding of HIV, a one-size fits all approach for HIV programming would be less effective and therefore targeted and case specific approaches need to be utilized.…”
Section: Resultssupporting
confidence: 91%
“…Yet in other settings, particularly general out-patient services, reaching high PITC coverage has been challenging [7] due to several barriers related to resource limitations including personnel, training, infrastructure and commodities [8]. Thus, clinicians would often practice an informal risk screening, testing only those patients suspected of having AIDS-defining illness or risk behaviors [9]. Additional challenges around consent/guardianship, provider attitudes toward the likelihood of HIV infection, complexities of implementing robust index testing initiatives at scale, and the fact that some children may not be reached by index or other facility-based testing due to health utilization barriers have further limited testing coverage [10][11][12], and widened the treatment gap between children/adolescents and adults.…”
Section: Introductionmentioning
confidence: 99%